A thermal foot manikin as a tool for footwear evaluation and development. (March 2023) - West, Anna Maria; Oberst, Florian; Tarrier, James; Heyde, Christian; Schlarb, Heiko; Brüggemann, Gert-Peter; Hodder, Simon; Havenith, George
This study investigated the relationship between thermal perceptions during human wear trials and thermal foot manikin measurements of heat and vapour resistance for five running shoes varying in material and construction. Measurements of thermal/evaporative resistance were performed using a 12-zone sweating thermal-foot manikin. Eleven males performed running trials on five occasions, wearing shoes of same design, differing in materials and construction, to achieve a range of heat/vapour resistances and air permeabilities. Trials in 20°C/60% RH consisted of three phases: 15 min rest, 40 min running, 15 min recovery. In-shoe temperature/humidity were measured at two sites on the left foot. Thermal sensation/wetness perception/thermal comfort were provided for the left foot and four foot regions. Variations in shoe material and construction resulted in differences in thermal and evaporative resistance. These differences were reflected in in-shoe temperature and in-shoe absolute humidity assessed during wear trials. At the end of the rest period, thermal sensation was strongly related to thermal insulation ( r 2 = 0.69, p<0.001). During exercise however, thermal sensation, wetness perception and thermal discomfort were related to both thermal insulation and evaporative resistance. Thermal foot manikins provide a sensitive, effective evaluation of footwear thermal properties, which are also reflective of changes to in-shoe parameters during actual use. This discriminate power may be enhanced using higher, more realistic air-speeds during testing, as well as simulating foot movement. While thermal foot manikins are highly sensitive to design features/attributes of footwear (e.g. ventilation openings, air-permeabilities and coatings), subjective evaluations of footwear do not seem to have the same sensitivity and discriminative power.